Zingerone Inhibits the Neutrophil Extracellular Trap Formation and Protects against Sepsis via Nrf2-Mediated ROS Inhibition. (28th January 2022) - Zhu, Yingjie; Wang, Dexiang; Luo, Jingjing; Jie, Jing; Liu, Han; Peng, Liping; Bai, Xiaoxue; Li, Dan
Abstract : Neutrophils release chromatin and antimicrobial proteins to trap and kill microbes, which is termed as neutrophil extracellular trap (NET) formation. NETs play a pivotal role in host defense against infection. However, emerging evidence indicated that NETs also contribute to an exaggerated inflammatory response and organic injuries in sepsis. Zingerone, a natural compound extracted from Zingiber officinale, exerts antioxidant, anti-inflammatory, and antioncogenic properties. In this study, we found that treatment with zingerone reduced organ injury and improved the outcome in a cecal ligation puncture- (CLP-) induced polymicrobial sepsis model. Administration of zingerone also alleviates reactive oxygen species (ROS) accumulation and systematic inflammation in septic mice and inhibits neutrophil extracellular traps (NETs) formation in vivo and in vitro . Furthermore, inhibition of nuclear factor erythroid 2-related factor 2 (Nrf2) with its specific antagonist significantly counteracted the suppressive effects of zingerone on ROS and NETs and retarded the protective role of zingerone against sepsis-associated organ injury. In addition, exposure to zingerone does not affect phagocytic activity of neutrophils in vitro and bacterial dissemination in vivo. Above all, our results indicate that zingerone treatment obviously attenuates NET formation and inflammatory response via Nrf2-mediated ROS inhibition, thus providing a novel therapeutic strategy against sepsis-induced injury.